Analisis Pendekatan Feminisme dalam Lagu Rossa yang Berjudul "Cintai Aku" dan "Hey Ladies" - Hafni, Suci (Bastrando: Jurnal Bahasa dan Sastra Indonesia, 2024)
This research aims to analyze the messages contained in the two songs sung by Rossa, namely Cintai Aku and Hey Ladies using a feminist approach. The method used in this research is a qualitative descriptive method using listening and note-taking techniques. Literary works have several types, one of which is song. Songs are literary works to convey emotional and social messages through song lyrics. These two songs have different views on women's perspectives. The song entitled "Love Me" highlights women's emotional dependence on happiness and dignity for the sake of love. On the other hand, the song entitled Hey Ladies conveys a message of women's empowerment by inviting women to be more rational, independent, logical, intelligent and assertive in relationships. These findings were carried out to strengthen the importance of song lyrics as a medium in increasing awareness of issues of feminism and women's independence in society, especially in expressing feelings that are always oppressed. Based on the research conducted by the researcher, songs performed by Rossa show differences in the perspective of women. The song Cintai Aku portrays women as emotional, dependent, and willing to sacrifice themselves for love, reflecting gender inequality. On the other hand, the song Hey Ladies encourages women to be smart, independent, and not easily trapped in harmful relationships.